2021
DOI: 10.3390/su13020862
|View full text |Cite
|
Sign up to set email alerts
|

Mineral Resource Depletion Assessment: Alternatives, Problems, Results

Abstract: The depletion of non-renewable natural resources (primarily mineral and energy resources) and its assessment is a problem that is analyzed based on the concept of sustainable development. Mineral resource depletion assessment is particularly important for resource-based economies. It provides for assessing the impact of mineral asset disposal that results from the suspension or termination of operations conducted by a mining company due to insurmountable circumstances. The results of such an event will be mani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 22 publications
0
21
0
3
Order By: Relevance
“…In general, this figure ranged from 0.040 for Italy to 0.984 for Hungary. Also, there is interest to the indicator of the minimum possible duration of the sustainable energy saving by natural gas economic development in the future, which was calculated by Formula (18). For some countries it is quite high.…”
Section: Assessment Of Sustainable Energy Saving By Natural Gas Economic Development By Individual Countriesmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, this figure ranged from 0.040 for Italy to 0.984 for Hungary. Also, there is interest to the indicator of the minimum possible duration of the sustainable energy saving by natural gas economic development in the future, which was calculated by Formula (18). For some countries it is quite high.…”
Section: Assessment Of Sustainable Energy Saving By Natural Gas Economic Development By Individual Countriesmentioning
confidence: 99%
“…In addition, the need to reduce resource consumption may be related to the detrimental impact of their consumption on the environment [15,16]. Finally, an important reason justifying measures to reduce the use of non-renewable natural resources is the need to leave them for future generations [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…Due to the development of modern societies, technological progress and the constant widening of the availability of goods, it can be concluded that along with the exponentially growing population of the Earth, the level of consumption of mineral resources is also close to exponential [1]. The consumption of goods is also growing in countries where mineral resources (raw material base) are limited [2] or close to exhaustion [3]. At the same time, growing awareness of societies and pressure from environmental organizations mean that more and more importance is attached to sustainable development [4].…”
Section: Introductionmentioning
confidence: 99%
“…With an increase in consumer demand for extracted raw materials, it is necessary to increase the requirements for the completeness and complexity of the use of the mineral resource base, and to develop a new scientific and methodological approach to the broad recovery of mineral resources and their preservation [26][27][28]. It is of special importance for regions (countries) with limited resources [29][30][31].…”
Section: Introductionmentioning
confidence: 99%